THE PROBLEMS OF JÜRGEN HABERMAS’s DELIBERATIVE DEMOCRACY THEORY - Sidqi, Ahmad (RADIX: Jurnal Filsafat dan Agama, 2023)
Jürgen Habermas a German philosopher who adopts of Karl Marx’s thought in the social order. However, Habermas does not immediately accept of the raw Marx’s thought. Habermas with rationalism as the epistemology. The Critical Theory criticize the sciences positive as the science of economics, sociology, technology, psychology; and also philosophy. The sciences is not questioned the direction of the process of the community itself. In a critique of the ideology of Habermas through the role of basic ethics and adopt the Immanuel Kant’s thought. Habermas to a blurb about dialectical theory of hermeneutic action through Aufhebung (hermeneutics of philosophy and psychoanalysis). Habermas was critique to postmodernism that universal as hegemony and discriminative to getting a plural morality Habermas's critical theory is a kind of epistemology that seeks to mate between objectivity and subjectivity, between scientists and philosophers, between the ontentic and the articulate. Critical theory also tries to expose the traditional theory, because it positions the object as untouchable, as it is. So difficult to capture its meaning by humans. This makes the object seem very sacred and must be received unanimously. The democracy of Habermas is deliberative democracy. Deliberative democracy aims to find a middle ground between Western liberalism and Asian and Islamic communitism. This assumption is established in a democratic form in the form of an intensive political system and public sphere.